Online media and political participation: the case of Malaysia - Willnat, Lars; Wong, W. Joann; Tamam, Ezhar; Aw, Annette (Routledge, 2013)
This study is based on a survey of 526 adult Malaysians who were interviewed shortly before the 2008 national election about online media use, levels of political participation, and voting intentions. The goal was to document the role of online media in a society that controls political information in traditional media and, in turn, compels citizens to seek alternative news sources online. As predicted, the findings indicated that online media use was positively associated with higher levels of political participation among Malaysian voters. The use of and exposure to social networking sites, political blogs, political online videos, party websites, and political ads on cell phones showed strong associations with political activism. However, the use of political online media did not predict voters’ likelihood of voting.